Clinical feasibility of a play-based assessment of motor speech disorders in young children in Austria - Erlacher, Gertraud; Velleman, Shelley L.; Holzinger, Daniel (Frontiers in Communication, 2025)
BackgroundThere is a lack of valid measures for the differential diagnosis of childhood apraxia of speech (CAS) worldwide, especially ones that are suitable for young children. With newly developed assessments, one key question is their feasibility in a community clinical setting.AimThe aim of this study is to examine the feasibility of a play-based tool to assess CAS, using the “Language-Neutral Assessment of Motor Speech” (LAMS) as an example, trialing it for the first time in a German-speaking region.MethodsThis exploratory study is conducted as a series of single case descriptions (N = 7) with monolingual German-speaking children. The feasibility aspects of practicality, acceptance, and adaptation are examined. The collected data are processed solely descriptively with additional qualitative observations.ResultsThe practicality of a complete administration of the LAMS in a clinical setting is limited because it is time-consuming; however, acceptance by children and caregivers is high for most parts of the test. Adaptations to economize the time investment (primarily by omitting video analysis) seem possible without a significant reduction of quality.Conclusions and clinical implicationsImplementation of a flexible, playful assessment, such as the LAMS, in local clinical settings looks promising. In German-speaking countries, a German adaptation of the LAMS could fill a gap in the assessment of motor speech disorders in young, hard-to-test children. More data regarding reliability and validity are needed.